1979
DOI: 10.1113/jphysiol.1979.sp012761
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and sensory properties of the thalamic reticular neurones related to somatic sensation in rats.

Abstract: SUMMARY1. In urethane-anaesthetized rats, studies were made on unit discharges of neurones of the thalamic reticular nucleus (tr) receiving the somatosensory input. Such units were found distributed in a part of the tr (s-tr) surrounding the anterior and anterolateral borders of the ventrobasal nuclear complex (vb).2. A series of five to ten bursts of grouped discharges were elicited in the s-tr neurones as orthodromic responses to single shock stimulation of the medial lemniscus (ml) or the somatosensory cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Several thalamic regions have been reported to react to stimulation of more than one sensory modality, representing possible relay stations of cross-modal effects . Simultaneous visual and tactile stimulation activated neurons in the medial geniculate body (Wepsic, 1966) and reticular nucleus (Sugitani, 1979). Similarly, cross-modal interactions have been reported for the auditory thalamus (Komura et al, 2005).…”
Section: Discussionmentioning
confidence: 80%
“…Several thalamic regions have been reported to react to stimulation of more than one sensory modality, representing possible relay stations of cross-modal effects . Simultaneous visual and tactile stimulation activated neurons in the medial geniculate body (Wepsic, 1966) and reticular nucleus (Sugitani, 1979). Similarly, cross-modal interactions have been reported for the auditory thalamus (Komura et al, 2005).…”
Section: Discussionmentioning
confidence: 80%
“…Anatomic studies with retrograde and anterograde tracers showed that the neurons of the RNT receive topographicallyorganized collateral inputs from both the thalamo-cortical and the cortico-thalamic projections (Jones, 1975). Although the Golgi preparations (Scheibel & Scheibel, 1966) suggested that some RNT axons ramify widely throughout the thalamus, more recent electrophysiologic and anatomic studies indicate that neurons in particular regions of the RNT tend to project to the nearby parts of the thalamus (Hale et al, 1982;Sugitani, 1979;Montero, 1983) where they presumably act as inhibitory modulators (for review, see Jones, 1981). Further evidence for an inhibitory role for the RNT was provided by the demonstration that RNT neurons react immunocytochemically for glutamic acid decarboxylase (GAD), the major enzyme involved in the synthesis of gamma-aminobutyric acid (GABA) (Houser et al, 1980;Oertel et al, 1983;Ohara et aI., 1983).…”
Section: Discussionmentioning
confidence: 97%
“…Anatomical and physiological studies have shown that Rt cells are scattered throughout the Rt into sectors according to the modality of the sensory inputs (Montero et al, 1977;Pollin and Rokyta, 1982;Shosaku, 1985;Shosaku et al, 1984;Sugitani, 1979). Every sector (visual, somatosensory, auditory, motor, or limbic) receives axon collaterals from reciprocally connected thalamic nuclei and cortical areas and projects back only to the corresponding thalamic nuclei (Bourassa et al, 1995;Bourassa and DeschĂȘnes, 1995;Fitzgibbon, 1994;Fitzgibbon et al, 1995;Hale et al, 1982;Harris, 1987;Jones, 1975;Minderhood, 1971;Ramon y Cajal, 1909-11;Scheibel and Scheibel, 1966;Steriade et al, 1984;Tai et al, 1995;Van Groen and Wyss, 1995;Velayos et al, 1989).…”
mentioning
confidence: 94%